Macaws, their behavior, and local biodiversity as possible drivers of ecotourism development in Alta Floresta, MT, Brazil - Cassel, Monica (Revista Ambientale, 2023)
The city of Alta Floresta, Mato Grosso State, Brazil, has a growing ecotourism industry. It has become a popular destination for birdwatching in the country and represents a hotspot for Amazonian tourism in Mato Grosso State. The region is home to a variety of macaw species. This study therefore sought to determine any associations between species behavior and tourism seasonality in the region. Approximately 50 nests were located in this study through scientific expertise and crowdsourcing. Two species—the blue-and-gold macaw (Ara ararauna) and the red-and-green macaw (A. chloropterus)–were found to engage in feeding and nesting behavior in the city. The nests were located in clean and well-maintained areas near the city center. The most frequent macaw sightings occurred between August and February, a period which coincided with academic and municipal events in the region. These findings may be used to guide strategies for birdwatching and species management, particularly in the case of macaws; they may also aid in environmental conservation efforts for these species’ habitats. This study will ideally be used in the creation of strategies to stimulate tourism in Alta Floresta and the surrounding region, and particularly to support activities focused on birdwatching and local biodiversity.